Strategy for the Use of Tahfidz Mentoring Methods at Maahad Tahfiz Vokasional Aman Bistari (MTVAB), Malaysia - Nana Wulandari; Nur Rohmah Hayati (ALSYS, 2025)
This study analyzes the strategies and methods of tahfiz mentoring implemented at Maahad Tahfiz Vokasional Aman Bistari (MTVAB), Malaysia, in integrating Qur’anic memorization with vocational education (TVET) to enhance students’ memorization quality, motivation, and time management. Adopting a qualitative case study design, data were collected from 26 purposively selected participants—including administrators, tahfiz teachers, and students—through interviews, observations, questionnaires, and document analysis. Data were processed using Miles and Huberman’s interactive analysis model, with validity ensured through triangulation and member checking. Statistical validation confirmed reliability using Pearson’s Product-Moment and Cronbach’s Alpha (α = 0.872). The findings indicate that mentoring strategies such as talaqqi, halaqah, tikrar, saba’, and manzil significantly improve memorization accuracy and consistency. Ninety percent of students reported enhanced memorization performance and focus, while 85% affirmed improved ability to balance tahfiz and vocational learning. Institutional support, peer mentoring, and digital media integration further reinforced students’ motivation and self-regulation. The study concludes that structured tahfiz mentoring effectively integrates spiritual development with technical competencies, offering a viable model aligned with Malaysia’s National Tahfiz Education Policy 2.0. It contributes to the discourse on harmonizing Qur’anic education with vocational training through innovative mentoring practices and collaborative learning environments.